(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Human behavior is based on emotions, they activate and organize the perception, thinking and aspirations of a person. Emotions are a powerful lever that helps to open the veil over the incomprehensible, broaden one’s horizons, acquire new skills, abilities, and knowledge. Emotions form the core of a person’s motivational structure. They influence our thoughts and actions in everyday life. Words are in continuous connection with our intellectual and emotional life. The subject-logical meaning of each word is surrounded by a special expressive atmosphere, which fluctuates depending on the context.